Antarctic Guardians: Commitment as a result of identity variables and ecological attitudes - Pallahuala,Esteban Sanchez (2022)
Abstract The research is interested in both ecological and identity (social) variables involved in increasing environmental commitment to Antarctic care. Two studies with inhabitants of two cities in the extreme south, and another with a national sample from three different geographical areas (north, center and south) participated by answering a self-administered survey. The instruments measured the perception of personal responsibility for Antarctic care in the present and future, Value of Antarctica, Antarctic regional ecological identity, and environmental beliefs. The core results show that identification with the Antarctic territory is important in determining the perception of responsibility and commitment to its care, and that this process is mediated by the value given to the polar continent. This mediation was observed in both the sample of locals and nationals. These results are discussed in relation to the importance of considering identity variables when developing models that aim to promote a pro-ecological attitude.